The afterlife of Holly Chase - Hand, Cynthia, 1978-; Dickens, Charles, 1812-1870. (New York, NY : HarperTeen, an imprint of HarperCollinsPublishers, 2017)
After being visited by three ghosts on Christmas Eve, Holly Chase chooses not to mend her spoiled ways. Upon her death Holly discovers her selfishness has caused her to work for eternity as a ghost of Christmas past. Every year Project Scrooge saves another miserly grouch, and Holly stays frozen at seventeen while her family and friends go on living without her. But this year, everything is about to change....
Keywords: Christmas stories; Death -- Juvenile fiction; Future life -- Juvenile fiction; Ghost stories; Selfishness -- Juvenile fiction; Christmas -- Fiction; Death -- Fiction; Ghosts -- Fiction; YOUNG ADULT FICTION / Ghost Stories; YOUNG ADULT FICTION / Romance / Paranormal; YOUNG ADULT FICTION / Social Themes / Death & Dying; Ghost stories; Death -- Fiction